Early Ongoing Speciation of Ogataea uvarum Sp. Nov. Within the Grape Ecosystem Revealed by the Internal Variability Among the rDNA Operon Repeats - Roscini, Luca; Tristezza, Mariana; Corte, Laura; Colabella, Claudia; Perrotta, Carla; Rampino, Patrizia; Robert, Vincent; Vu, Duong; Cardinali, Gianluigi; Grieco, Francesco (Frontiers in Microbiology, 2018)
A yeast strain was isolated during a study on vineyard-associated yeast strains from Apulia in Southern Italy. ITS and LSU D1/D2 rDNA sequences showed this strain not to belong to any known species and was described as the type strain of Ogataea uvarum sp.nov, a close relative of O. philodendri. Several secondary peaks appeared in the sequences, suggesting internal heterogeneity among the copies of the rDNA. This hypothesis was tested by sequencing single clones of the marker region. The analyses showed different levels of variability throughout the operon with differences between the rRNA encoding genes and the internally transcribed regions. O. uvarum and O. philodendri share high frequency variants, i.e. variants frequently found in many clones, whereas there is a large variability of the low frequency polymorphisms, suggesting that the mechanism of homogenization is more active with the former than with the latter type of variation. These findings indicate that low frequency variants are detected in Sanger sequencing as secondary peaks whereas in Next Generation Sequencing (NGS) of metagenomics DNA would lead to an overestimate of the alpha diversity. For the first time in our knowledge, this investigation shed light on the variation of the copy number of the rDNA cistron during the yeast speciation process. These polymorphisms can be used to investigate on the processes occurring in these taxonomic markers during the separation of fungal species, it being a genetic process highly frequent in the complex microbial ecosystem existing in grape, must and wine.